Effect of physicochemical pretreatments plus enzymatic hydrolysis on the composition and morphologic structure of corn straw. (August 2019) - Wang, Ping; Liu, Chaoqi; Chang, Juan; Yin, Qingqiang; Huang, Weiwei; Liu, Yang; Dang, Xiaowei; Gao, Tianzeng; Lu, Fushan
Abstract: In order to decrease corn straw crystallinity for improving reducing sugar yield, physicochemical pretreatments plus enzymatic hydrolysis were investigated. The results showed that hemicellulose and lignin degradation rates in corn straw treated with physical method (ultrasound wave (group 12), extrusion + ultrasound wave (group 14), extrusion + ultrasound wave + microwave (group 15)) combined with chemical compounds (lime + sodium hydroxide + hydrogen peroxide) were significantly higher than the untreated corn straw ( P  < 0.05). After the above three physicochemical pretreatments were fulfilled and followed by enzymatic hydrolysis, the cellulose, hemicelluloses, lignin degradation rates and reducing sugar yield were respectively increased by 51.38%, 82.44%, 64.63% and 378.86% in group 12, 69.61%, 86.05%, 62.88% and 421.77% in group14, 61.59%, 74.51%, 56.19% and 425.98% in group 15, compared with the untreated corn straw ( P  < 0.05). The scanning electron microscope showed that straw structure treated with extrusion + ultrasonic + chemical pretreatment was more seriously damaged than that with single physical or chemical pretreatment. The different sequences of physicochemical treatments had different effects on corn straw degradation. It could be concluded that the optimal physicochemical pretreatments plus enzymatic hydrolysis were effective for corn straw degradation and reducing sugar yield. Highlights: Chemical and physicochemical pretreatments were better than physics for straw degradation. Different physicochemical treatment sequences had different effects on straw degradation. Physicochemical pretreatments plus enzymatic hydrolysis were effective for straw degradation.